2016
DOI: 10.1016/j.scitotenv.2016.06.169
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate community assembly in pools created during peatland restoration

Abstract: Many degraded ecosystems are subject to restoration attempts, providing new opportunities to unravel the processes of ecological community assembly. Restoration of previously drained northern peatlands, primarily to promote peat and carbon accumulation, has created hundreds of thousands of new open water pools. We assessed the potential benefits of this wetland restoration for aquatic biodiversity, and how communities reassemble, by comparing pool ecosystems in regions of the UK Pennines on intact (never drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
12
1
Order By: Relevance
“…Höper et al, 2008) where peatlands have been damaged by artificial drainage, ditches in United Kingdom peatlands are being blocked. This restoration activity results in the creation of thousands of small pools within the blocked ditches, which in sum can amount to a large area of open water (Brown, Ramchunder, Beadle, & Holden, 2016;Holden et al, 2017;Parry, Holden, & Chapman, 2014). It is not known to what extent the hydrological functioning of these artificial peatland pools is similar to that of natural pools.…”
mentioning
confidence: 99%
“…Höper et al, 2008) where peatlands have been damaged by artificial drainage, ditches in United Kingdom peatlands are being blocked. This restoration activity results in the creation of thousands of small pools within the blocked ditches, which in sum can amount to a large area of open water (Brown, Ramchunder, Beadle, & Holden, 2016;Holden et al, 2017;Parry, Holden, & Chapman, 2014). It is not known to what extent the hydrological functioning of these artificial peatland pools is similar to that of natural pools.…”
mentioning
confidence: 99%
“…Like other aquatic macroinvertebrates, dragonflies show very sudden positive responses to rewetting (Brown et al ), while species fluctuations depend mostly on pond quality. Almost no dragonflies are found in degraded, dry, and shaded peatlands, while they immediately colonize rewetted sites with unshaded water bodies (Elo et al ) as created by peat extraction for dam building.…”
Section: Discussionmentioning
confidence: 99%
“…For example, open water pools, that are created during peatland rewetting, are used by aquatic macroinvertebrates like Coleoptera and Odonata (Brown et al 2016). Increased soil moisture benefits craneflies (Carroll et al 2011), and a raised water table and improved tree stand structure favor mire ants (Punttila et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies examining wetland birds, invertebrates, and amphibians have found evidence of positive change in population abundance or species presence, although these changes are not necessarily sustained over time (Brown, Smith, & Batzer, 1997;Hapner et al, 2011;Ruhi et al, 2012). Restored peatlands have been shown to support freshwater communities comparable with those in natural wetlands (Brown, Ramchunder, Beadle, & Holden, 2016). Created compensatory wetlands often fail to achieve the same ecosystem functions as restored or rehabilitated natural wetlands (Brown & Veneman, 2001;Español, Gallardo, Comín, & Pino, 2015;Spadafora et al, 2016;Whigham, 1999).…”
Section: Wetland Restoration and Creationmentioning
confidence: 99%